Cardiovascular Dysregulation in Heat Stroke Driven by Climate Change: Pathophysiology and Clinical Implications - Nayla Prima Dyta; Ativa Muthia Diniyah; Andi Safa Natasya Lukman; Nadine Khaira Zahratunnisa Abdul; Fatmawati Adelia Pakaya; Sri Manovita Pateda (Jurnal Kolaboratif Sains, 2025)
Heat stroke is an escalating global health threat driven by rising temperatures and increasingly frequent heat waves. This study aimed to elucidate the mechanisms by which extreme heat exposure precipitates cardiovascular injury and hemodynamic collapse, and to identify biomarkers predictive of poor outcomes. A mixed-methods design integrating ecological time-series analysis with a prospective clinical cohort was employed. Distributed Lag Non-linear Models were used to quantify the association between ambient temperature and cardiovascular mortality over a 20-year period, showing a 2.1% increase in risk per 1°C temperature rise above local thresholds. Clinically, 70% of heat stroke patients demonstrated elevated troponin levels above the 99th percentile, while 55% exhibited BNP elevation. Inflammatory markers such as IL-6 (>80 pg/mL) and D-dimer (>1.5 µg/mL) were strongly associated with progression to multi-organ dysfunction. Hemodynamic assessments revealed an early hyperdynamic state followed by reduced ejection fraction and hypotension within 24–36 hours, consistent with myocardial stunning. Atypical presentations, including ventricular fibrillation with normal surface temperature, underscored diagnostic challenges and highlighted the importance of core-temperature monitoring. These findings indicate that cardiovascular failure in heat stroke arises from both thermoregulatory overload and direct myocardial injury, compounded by systemic inflammation and coagulopathy. The study contributes new insights into biomarker-driven risk stratification and emphasizes the need for precision diagnostic tools and enhanced public health interventions in an era of intensifying climate stress.